New horizons for the in vivo assessment of major aspects of bone quality: microstructure and material properties assessed by Quantitative Computed Tomography and Quantitative Ultrasound methods developed by the BioAsset consortium - Glüer, Claus C. (2013)
The Biomechanically founded individualised osteoporosis Assessment and treatment (BioAsset) consortium pursues experimental and clinical studies in the context of skeletal effects of bisphosphonate treatment. Here, first results using newly developed diagnostic methods in a set of vertebral bone specimen obtained from donors with documented bisphosphonate history ranging from 0 to more than 5 years of treatment are presented. A new thoracolumbar quantitative computed tomography (QCT) protocol covering T6 to L4 plus high-resolution QCT (HRQCT) assessment of T12 were compared with high-resolution peripheral QCT (HRpQCT) and micro-CT scans of excised specimens serving as gold standard techniques. Finite element (FE) modelling was performed. Material, ultrastructural, and micromechanical properties were tested on a set of single trabeculae obtained from the donor specimens. A newly developed quantitative ultrasound (QUS) device for measuring the anisotropy of cortical material properties was designed and built. The thoracolumbar QCT protocol permitted in situ imaging with good image quality and automated segmentation of vertebral bodies in the whole range from T6 to L4. The duration of bisphosphonate treatment was significantly associated with increased levels of mineralization and this effect could be measured with HRQCT performed on excised specimens. Microstructural parameters contributed to vertebral bone strength modelled by FE analysis independently of bone mineral density. The new QUS scanner permitted measuring the acoustical anisotropy of reference materials. Taken together, these results document that new methods developed in BioAsset permit a more comprehensive assessment of bone fragility. The set of donor specimens with a documented history of bisphosphonate treatment allows for the assessment of the effects of long-term treatment from the organ down to the tissue and material level. These results will ultimately be linked to the parallel clinical study to provide guidance for determining the optimum duration of bisphosphonate treatment to reduce the incidence of osteoporotic fractures.